Anaerobic phototrophic processes of hydrogen production by different strains of microalgae Chlamydomonas sp. Issue 9 (24th March 2018) - Vargas, Sarah Regina; Santos, Paulo Vagner dos; Giraldi, Laís Albuquerque; Zaiat, Marcelo; Calijuri, Maria do Carmo
Abstract: Hydrogen is an abundant element and a non-polluting fuel that can be biologically produced by microalgae. The aim of this research was to investigate biological hydrogen production by Chlamydomonas reinhardtii (CC425) and Chlamydomonas moewusii (SAG 24.91) by direct biophotolysis in batch cultures. Strains were cultivated in TAP growth medium (pH 7.2) in two phases: in the first stage, cultures were maintained in an aerobic condition until the middle of the exponential phase; in the second stage, the biomass was transferred to closed anaerobic photobioreactors under sulfur deprived. Gas chromatography and Gompertz model were used to measure the hydrogen production and hydrogen production rate, respectively. We noticed that maximum hydrogen production by biomass of C. reinhardtii was 5.95 ± 0.88 μmol mg −1 and the productivity was 17.02 ± 3.83 μmol L −1 h −1, with hydrogen production five times higher than C. moewusii, approximately, though, C. moewusii obtained a higher ethanol yield compared to C. reinhardtii. The hydrogen production method, with the cultivation of strains in two different phases and sulfur deprivation, was effective for obtaining of biohydrogen for Chlamydomonas ; however, it depends on the species, strain and growth conditions. Abstract : Chlamydomonas reinhardtii had five times higher hydrogen production compared to Chlamydomonas moewusii, with cultivation in two different phases and sulfur deprivation; however, it depends on the species and growth conditions.